Visual N80 latency as a marker of neuropsychological performance in schizophrenia: evidence for bottom-up cognitive models - Hever, Felix; Sahin, Derya; Aschenbrenner, Steffen; Bossert, Magdalena; Herwig, Kerstin; Wirtz, Gustav; Oelkers-Ax, Rieke; Weisbrod, Matthias; Sharma, Anuradha (Clinical neurophysiology, 2021)
Objective - Cognitive deficits and visual impairment in the magnocellular (M) pathway, have been independently reported in schizophrenia. The current study examined the association between neuropsychological (NPS) performance and visual evoked potentials (VEPs: N80/P1 to M- and P(parvocellular)-biased visual stimuli) in schizophrenia and healthy controls. - Methods - NPS performance and VEPs were measured in n = 44 patients and n = 34 matched controls. Standardized NPS-scores were combined into Domains and a PCA (Principal Component Analysis) generated Composite. Group differences were assessed via (M)ANOVAs, association between NPS and VEP parameters via PCA, Pearson’s coefficient and bootstrapping. Logistic regression was employed to assess classification power. - Results - Patients showed general cognitive impairment, whereas group differences for VEP-parameters were non-significant. In patients, N80 latency across conditions loaded onto one factor with cognitive composite, showed significant negative correlations of medium effect sizes with NPS performance for M/P mixed stimuli and classified low and high performance with 70% accuracy. - Conclusion - The study provides no evidence for early visual pathway impairment but suggests a heightened association between early visual processing and cognitive performance in schizophrenia. - Significance - Our results lend support to bottom-up models of cognitive function in schizophrenia and implicate visual N80 latency as a potential biomarker of cognitive deficits in schizophrenia.